2016
DOI: 10.5539/ijbm.v11n6p296
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Public Mutual Funds (PMFs) in Emerging Economies: A Case of Bangladesh

Abstract: Public Mutual fund (PMF) is an instrument for pooling the funds by issuing units to the investors and investing funds in the capital market to achieve their objectives. To invest in mutual funds is a complicated trade for investors as individual assets are belongs to verity of risks and they are dubious on return on investment. There are only 43 Mutual Funds are available to choose from where the investors can invest. To take the investment decision, the investors need to know which funds are performing better… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Thus far, there are quite a few studies that investigated some aspects of Islamic mutual funds. These studies mainly focus on their performance and risk/return features (Abedifar, et al, 2015;Barakat 2011;Dewri, et al, 2016;Ashraf 2013). Interestingly, however, these studies also found that Islamic funds generally outperform their counterpart conventional ones.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, there are quite a few studies that investigated some aspects of Islamic mutual funds. These studies mainly focus on their performance and risk/return features (Abedifar, et al, 2015;Barakat 2011;Dewri, et al, 2016;Ashraf 2013). Interestingly, however, these studies also found that Islamic funds generally outperform their counterpart conventional ones.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, there are quite a few studies that investigated some aspects of Islamic mutual funds. These studies mainly focus on their performance and risk/return features (Abedifar, et al, 2015;Barakat 2011;Dewri, et al, 2016;Ashraf 2013). Interestingly, however, these studies also found that Islamic funds generally outperform their counterpart conventional ones.…”
Section: Introductionmentioning
confidence: 99%